Cooperative tracking in camera sensor networks with sliding mode control. (17th January 2023) - Kameoka, Yoshihiro; Hayashi, Naoki; Takai, Shigemasa
Abstract : This paper presents robust cooperative tracking control in camera sensor networks. We consider a camera sensor network with a Pan-Tilt (PT) mechanism whose dynamics is expressed as the Euler–Lagrange equation. We propose a distributed control law based on sliding mode control to achieve cooperative target tracking. The stability of the closed-loop system is conducted by Lyapunov's stability theory considering discontinuities of the control input. We also verify the effectiveness of the proposed method with a numerical example of synchronization of a PT camera sensor network under external disturbance. GRAPHICAL ABSTRACT: UF0001